Smart Admissions: Meningkatkan Efesiensi Proses Penerimaan Mahasiswa Baru dengan Chatbot Interaktif - Asmaul Husna RS; Adawiyah Asti Khalil; Mindi Richia Putri; Muhammad Ari Rifqi; Ari Kurniawati (Jurnal Teknologi Informasi dan Multimedia, 2026)
The new student admission (PMB) process at the Baru Universitas Bima Internasional MFH often faces challenges related to time efficiency and administrative burdens due to repetitive inquiries from prospective students. This research aims to design and build an interactive chatbot system named "Sipenmaru MFH" to enhance the efficiency and effectiveness of the PMB process. The de-velopment method used is Extreme Programming (XP), which allows for an adaptive and flexible process. Data was collected through interviews and questionnaires to build the chatbot's knowledge base. The application was developed using the Flutter framework with a NoSQL da-tabase, and its functionality was tested using the Black Box testing method. The result of this re-search is a functional chatbot application with a user-friendly interface, capable of providing fast and accurate responses to common questions regarding new student admissions. The implemen-tation of this chatbot has successfully provided easier access to information for prospective stu-dents and reduced the committee's workload, thus making the admission process more efficient.